2022
DOI: 10.2217/pmt-2022-0037
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block Versus Transversus Abdominis Plane Block In Laparoscopic Hysterectomy

Abstract: Background: The objective was to determine whether an erector spinae plane (ESP) block could provide additional postoperative analgesic benefits compared with a transversus abdominis plane block. Methods: 78 patients were separated into two groups (n = 39 per group). Both groups received bilateral injections of 266 mg Exparel® (20 ml) and 60 ml of 0.125% bupivacaine. Patients undergoing a transversus abdominis plane block received these injections intraoperatively, while patients undergoing an ESP block receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A study by Kamel et al 19 found lower morphine consumption in patients receiving ESP compared to TAP blocks after total abdominal hysterectomy, but there was no difference in postoperative nausea and vomiting. A study conducted by Warner et al 24 in patients presenting for laparoscopic hysterectomies, showed no significant difference in pain scores, opioid consumption, or patient satisfaction between ESP and TAP blocks.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study by Kamel et al 19 found lower morphine consumption in patients receiving ESP compared to TAP blocks after total abdominal hysterectomy, but there was no difference in postoperative nausea and vomiting. A study conducted by Warner et al 24 in patients presenting for laparoscopic hysterectomies, showed no significant difference in pain scores, opioid consumption, or patient satisfaction between ESP and TAP blocks.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Kamel et al19 found lower morphine consumption in patients receiving ESP compared to TAP blocks after total abdominal hysterectomy, but there was no difference in postoperative nausea and vomiting. A study conducted by Warner et al24 in patients presenting for laparoscopic hysterectomies, showed no significant difference in pain scores, opioid consumption, or patient satisfaction between ESP and TAP blocks.A study by Hassanin et al25 on emergency laparotomies, showed lower cumulative fentanyl consumption in the ESP vs TAP group but the study did not assess differences in opioidrelated side effects or patient satisfaction. A meta-analysis by Liheng et al26 comparing ESP and TAP blocks for abdominal surgery found ESP blocks lowered opioid consumption and pain scores statistically but did not reach clinically significant targets.…”
mentioning
confidence: 96%